Novel Carbon Black-Halloysite Nanotube Reinforced NBR-PVC Hybrid Oil Seals for Automotive Applications - Senthilvel, K.; Prabu, B. (Recent Patents on Materials Science, 2018)
Background: The current scenario requires the rubber industries to develop cheaper and environmentally friendly fillers as an alternative to the conventionally used carbon black filler. Objective: This study aims at developing new NBR/PVC oil seals for automotive applications using CB-HNT hybrid fillers. Method: In various patents, FESEM and XRD were used to study the microstructure of the samples. Tensile and tear tests were conducted by using a universal testing Machine. Hardness and compression set were studied using shore a hardness tester and compression set. Thermogravimetric analysis is used to evaluate the thermal stability of the samples. Results: The tensile strength, elongation at break, 100% modulus, tear strength and swelling resistance of the NBR/PVC hybrid nanocomposites are increased by 12.87%, 13.91 %, 14.65%, 33.58%, and 25.9 %, respectively compared to the conventional composites. Hardness and compression set of the nanocomposites had improved significantly. Incorporation of HNT in carbon black filled NBR/PVC composites improved the thermal stability with an increment of 4.42 °C in the maximum degradation temperature. XRD and FESEM studies reveal the intercalation of NBR/PVC chains, CB and other ingredients into the HNT galleries and formation of intercalated structures. Conclusion: The results demonstrate that the synergistic effect of CB-HNT hybrid fillers, improved NBR/PVC-CB-HNT interfacial interactions and formation of intercalated structures are believed to be responsible for the superior mechanical properties, swelling resistance and thermal stability of the NBR hybrid nanocomposites.
Keywords: swelling resistance